Write in the fog: narratives and representations about COVID during the first half of 2020 in Argentina - M. R. Fiquepron (Ибероамериканские тетради)
Since its inception as a global pandemic, COVID-19 has been the subject of multiple appropriations around the world. With the possibility of writing and sharing information open due to current technological developments and digital media, a series of publications focused on reflecting on the impact of the pandemic around the world circulated during the first months of 2020.The aim of this article is to analyze these publications, taking them as a valuable input to delve into the reflections that, from culture and social sciences, emerged on the pandemic. What can these articles show us, already more than two years after being published? What were the main ideas, concerns and diagnoses? Beyond these questions, we are also interested in investigating the construction of a network of meanings and notions that began to be associated with the disease and that, in its pandemic context, we believe is highly relevant to understanding the meanings that were incorporated into this new virus as it spread across the globe.